Bystander Selection for Antimicrobial Resistance: Implications for Patient Health. Issue 10 (October 2019) - Morley, Valerie J.; Woods, Robert J.; Read, Andrew F.
Abstract : Antimicrobial therapy promotes resistance emergence in target infections and in off-target microbiota. Off-target resistance emergence threatens patient health when off-target populations are a source of future infections, as they are for many important drug-resistant pathogens. However, the health risks of antimicrobial exposure in off-target populations remain largely unquantified, making rational antibiotic stewardship challenging. Here, we discuss the contribution of bystander antimicrobial exposure to the resistance crisis, the implications for antimicrobial stewardship, and some novel opportunities to limit resistance evolution while treating target pathogens. Highlights: Antimicrobial therapy enriches for resistance in off-target microbiota. For some pathogen species, off-target antimicrobial exposure may be a major driver of antimicrobial resistance. Antimicrobial therapy is a risk factor for subsequent infection with resistant organisms. Enrichment for resistance in off-target microbiota likely contributes to this risk. Off-target antimicrobial exposure can be managed through traditional stewardship methods like reducing unnecessary antibiotic prescriptions, but quantitative data necessary to optimize patient treatment and evolutionary risk mitigation are generally lacking. Novel adjunctive therapies that shield the microbiome from antimicrobials offer one way to mitigate off-target selection.